Psycho-social impact of stillbirths on women and their families in Tamil Nadu, India - a qualitative study - Vijayaprasad Gopichandran; Sudharshini Subramaniam; Maria Jusler Kalsingh (BMC, 2018)
Abstract Background Stillbirth has serious psycho-social consequences on the parents and on the family. The psychological impact of stillbirth is strongly influenced by the social and cultural context. There is very scarce information on this from the Indian context. This qualitative study was conducted to understand the psycho-social impact, aggravating factors, coping styles and health system response to stillbirths. Methods A qualitative study was conducted using in-depth interviews with mothers who experienced stillbirth in the past 1 year and their families. A total of 8 women and two health care providers were interviewed by trained interviewers. The interviews were transcribed into the local language and thematic analysis was performed by the researchers retaining the transcripts in the local language. Themes were identified, and a conceptual framework was developed. Results Women who experienced stillbirths suffered from serious forms of grief and guilt. These emotions were aggravated by the insensitive health system, health care providers, friends, and neighbours, as well as strained marital relationship and financial burdens. The women and their families were disturbed by the 'suddenness' of the stillbirth and frantically searched for the cause. They were frustrated when they couldn't find the cause and blamed various people in their lives. The women and their families perceived poor quality of services provided in the health system and reported that the health care providers were inconsiderate and insensitive. On the other hand, the health care providers reported that they were over-worked, and the health facilities were under-staffed. The community health workers reported that they felt caught in the crossfire between the health facility staff and the family who suffered the stillbirth. The women reported several coping mechanisms including isolation, immersion in work, placing maternal love on other children, the anticipation of next pregnancy and religiosity. Conclusion Stillbirth is a major cause of psycho-social morbidity. Health systems should be responsive to the psycho-social needs of women who suffer stillbirths and their families.